Investigating The Factors Affecting The Adoption of Solar Energy: A Synthesis of TAM ‎and TPB among Households - Dubey, Shampy; Kirti; Katoch, Rupinder; Rehman , Muzzamil; Kaur , Prabhjeet (International Journal of Accounting and Economics Studies, 2025)
The demand of going green with green energy in the global context has risen the significance ‎of household behavioral aspects towards utilization of solar energy. The infrastructural ‎difficulties and behavioral obstacles have influenced the demand of sustainable energy ‎alternatives. Residential areas are adopting solar energy systems as an unconventional energy ‎source. To examine the effects behavioral and technological factors on the adoption of solar ‎energy systems at the household level. In this research, the quantitative method was used and ‎was based on the Technology Acceptance Model (TAM) and the Theory of Planned Behavior ‎‎(TPB). The model aimed at analyzing the extent to which Solar Perceived Usefulness (SPU), ‎Perceived Ease of Use (PEU), Attitude (A), Subjective Norm (SN) and Perceived Behavioral ‎Control (PBC) had significant effects on Behavioral Intention to Adopt Green Energy ‎‎(BIAGE) and Use Behavior (UB) among households. SmartPLS was used to test the structural ‎model utilizing the data which was gathered in households in the state of Bihar. The results of ‎the empirical studies showed that the Attitude, Subjective Norm, and Perceived Behavioral ‎Control had a strong impact on the Behavioral Intention that further influenced the Use ‎Behavior. Furthermore, it was discovered that Perceived Ease of Use and Solar Perceived ‎Usefulness positively and significantly affected Attitude and Behavioral Intention account 36.1 ‎percent. The results support the integrative potentials of TAM and TPB in explaining the ‎behavior intentions of adopting solar energy. Through the research work, a contribution has ‎been made to the extant discourse on the energy shifts to sustainability, with the social ‎influence, attitudinal positivity and perception and control of behavior all playing a composite ‎role toward establishing the intent towards household adoption‎.
Keywords: Solar Energy Adoption; Technology Acceptance Model (TAM); Theory of Planned Behavior ‎‎(TPB); Behavioral Intention, Renewable Energy; Household Adoption